Exploring the Effect of Physical Delivery V/S Cash Settled Futures Contracts with the Prospective of Obligatory Delivery in Islamic Contract of Sales - Adil, Farzan; Siddiqui, Danish Ahmed (International Journal of Social and Administrative Sciences, 2019)
This study emphasizes that either physical delivery or cash settlement method for futures contract is better for precious metal such as gold and the storable commodities like rice, wheat, sugar, as well as check the effect of both settlement method on the volatility of futures and spot price. To examine the issue we use bivariate GARCH model to discover the interaction between the spot price return and futures price return. The result shows basis variability of spot price and futures prices returns was substantially reduced in the case of physical delivery as compare to the cash settlement of same commodities, which means the physical delivery is more reliable for the rice, wheat, sugar, and gold futures contracts. In addition, physical delivery settlement method is better than the cash settlement because it covers the gap of demand and supply in the market which effect on price and the physical delivery method is more reliable, as it restricts the liquidation of futures contact which declines the price and provide the social benefit as well.